2002
DOI: 10.1103/physrevb.65.212101
|View full text |Cite
|
Sign up to set email alerts
|

Antiferrodistortive phase transition inPb(Ti0.48Zr0.52

Abstract: Ranjan et al. ͓Phys. Rev. B 65, 060102͑R͒ ͑2002͔͒ have recently presented results of a powder neutrondiffraction study of the high-temperature monoclinic (F M HT ) to low-temperature monoclinic (F M LT ) phase transition in Pb(Ti 1Ϫx Zr x )O 3 discovered by Ragini et al. ͓Phys. Rev. B 64, 054101 ͑2001͔͒. They attribute the presence of superlattice reflections in the diffraction data to tilting of oxygen octahedra and propose a monoclinic space group Pc for the F M LT phase. It is shown that for the model propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 9 publications
(6 reference statements)
10
63
0
1
Order By: Relevance
“…This is in agreement with the observations of a low temperature superstructure phase Cc already described by Hatch et al 5 and Pandey and Ragini 6 since the superlattice reflections cannot be observed in these measurements. ͑II͒ In an intermediate range around room temperature a changeover of the dominating symmetry takes place, marking the transition between the growth of nanodomains to tetragonal microdomains.…”
Section: ͑I͒supporting
confidence: 82%
See 2 more Smart Citations
“…This is in agreement with the observations of a low temperature superstructure phase Cc already described by Hatch et al 5 and Pandey and Ragini 6 since the superlattice reflections cannot be observed in these measurements. ͑II͒ In an intermediate range around room temperature a changeover of the dominating symmetry takes place, marking the transition between the growth of nanodomains to tetragonal microdomains.…”
Section: ͑I͒supporting
confidence: 82%
“…2͑f͔͒. This indicates a crystal structure change with composition to the antiferrodistortive low temperature phase reported as Cc 5,6 or R3c. 22 For undoped PZT, Pandey et al 11 reported this phase transition to occur at around 200 K.…”
Section: Temmentioning
confidence: 99%
See 1 more Smart Citation
“…La direction de la polarisation dans cette phase se situe entre les directions [001] Q et [111] R et cela pourrait expliquer la forte réponse piézoélectrique [4]. Très récemment, une seconde phase monoclinique stable à basse température (F M -groupe d'espace Cc) a été mise en évidence [5]. Cette phase est obtenue à partir de la phase F M (Cm) par rotation des octaèdres (Zr,Ti)O 6 avec, comme conséquence, le doublement de la maille.…”
Section: Les Solutions Solides Pbzr1-xtixo3 (Pzt) -L'état De L'artunclassified
“…As discussed above, this same transition may also occur along the PZ-PFN binary join and would give a stability field for the R3c structure extending into the ternary system at room temperature. In the stability field of the monoclinic structure below the MPB of PZT, the same octahedral tilting transition involves the symmetry change Cm-Cc [57][58][59][60][61][62], but no information is yet available to determine whether this occurs in the ternary system as well. In (Pb 0.94 Sr 0.06 )(Zr 0.55 Ti 0.…”
Section: Ternary Compositionsmentioning
confidence: 99%